PENGARUH PENGAWASAN MASYARAKAT TERHADAP PENGELOLAAN DANA DESA DI DESA KAYUUWI SATU KEC. KAWANGKOAN BARAT - LOLOWANG, FRISIANE; ROMPAS, WELSON; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2018)
This study aims to determine and analyse the magnitude of the influence of Community Monitoring on FundManagement Village in Kayuuwi Village 1. Most of the people of Indonesia live and live in rural areas, sothat the direction of policy and national development planning directed to the countryside. The method thatwriter use in this research is quantitative method, is research method based on philosophy of positivism, usedfor researcher on population or sample .Teknik sampling technique is a simple random sampling fromresearch in Village Kayuuwi 1 as much 50 people. Data analysis techniques used are simple linear regressionanalysis and simple correlation analysis of Community Monitoring as measured by Preliminary Supervision,On-Work Monitoring Ongoing, and Feedback Supervision. Shows that involvement in the oversight of villagefund management influences can be seen based on the indicators used that the community is always involvedor participating in the supervision of any village funding development and management project. The successof village development is measured based on the application of appropriate procedures in every developmentfunded by village funds so that better development of the village will be improved.Keywords: Supervision, Village Fund Management, Community.